i need to solve this formula for the specified variable of s.
c=(1/3)f(s+k) for s
c = (1/3)f(s + k)
First, multiply both sides of the equation by 3 to get rid of the leading coefficient, (1/3), on the right-hand side of the equation:
3·(c) = 3·((1/3)f(s + k))
3c = (3/3)f(s + k)
3c = f(s + k)
Divide both sides of the equation by f:
(3c)/f = (f(s + k))/f
3c/f = (f/f)(s + k)
3c/f = s + k
Subtract k from both sides of the equation to solve for s:
(3c/f) - k = (s + k) - k
(3c/f) - k = s
I'm assuming f is just a variable here, and not meaning a function of some variable s+k. In that case, I would need more information like what the function is.
c = (1/3)f(s+k)
Let's multiply out the right hand side to easily get access to our variable s.
c = (1/3)fs + (1/3)fk
Subtract (1/3)fk from each side.
(1/3)fs = c - (1/3)fk
Multiply each side by 3.
fs = 3c - fk
Here, we'll have to assume that f does not equal 0 and is never equal to 0. Divide both sides by f.
s = (3c/f) - k
And here is our answer, s in terms of our other given variables.